TEACHERS’ PERSPECTIVE TOWARD STUDENTS’ ETHIC IN ONLINE CLASSROOM BASED ON FOUR PRINCIPLES OF ETHICS - Feriyanti Elina Gultom; Ade Aini Nuran (BAHAS, 2021)
Abstract The purpose of this study is find out the teacher's perspective toward students’ ethics in online classrooms based on four principles of ethics. In this study, researcher elaborate and describe the data by using qualitative research method and data collection techniques in the form of interviews and questionnaire. The results of this study show 53% of respondent agree that students has a great confidentiality. It means that students be able to keep their individual work in original term and do not do plagiarism or cheated with their friends. Then, 55% of respondent is agree that their students has a good responsibility in online classroom. In the term of conflict of interest, teacher judge that students can’t prioritize the learning process in online classroom. From the result of questionnaire, 45% respondent said that most of students can’t give their attention and prepare their selves to online classroom. The last is honesty. From the result, there are 43% respondent that choose don’t agree that their students has a sense of honesty. The result that was gathered from interview and questionnaire show the similiar result. Both of those result show that teachers’ assess that their students has a good confidentiality. It is because students be able to collect their task by theirselves which mean they have a good confidentiality. Students has a good responsibility, keep the politeness and manner in online classroom, such as joining the class on time and collect their task on time. But in term of conflict of interest, students don’t give all of their attention to class, can’t keep their focus to class because of some disturbance from their environment. Some of students also don’t prepare a supportable facilities to online classroom so they can’t join the class. Students also don’t prepare their appearance as neat as in the offline classroom. Teachers also state that their students still do copy paste from internet and their friend’s task. It means they are lack of honesty.Keywords: Ethic, Perspective, Students, Teacher